Analisis Bibliometrik Tentang Mitigasi Bencana dan Pembangunan Berkelanjutan: Inisisasi Kebijakan Untuk Indonesia - Haris, Abd; Tahir, Supratman; Nurjaya, Muhammad; Baharuddin, Tawakkal (Universitas Indo Global Mandiri, 2023)
This research aims to analyze trends related to disaster mitigation and sustainable development policies through a bibliometric approach, with a special focus on implications and recommendations relevant to Indonesia. The analysis method involves searching and collecting data from Scopus, followed by data processing using the Vosviewer and Nvivo 12 Plus analysis tools. Research findings show an increasing trend in publications related to disaster mitigation and sustainable development since the early 2000s, reflecting increasing global awareness of the need for holistic and sustainable disaster management. Policy recommendations include strengthening early warning systems, developing disaster-resistant infrastructure, disaster awareness education and training, consolidating data and information, and collaboration between sectors and international partners. These are important steps in facing disaster challenges and encouraging sustainable development in Indonesia. Through an analytical approach that is bibliometrically rigorous, this research identifies knowledge gaps in the global literature related to the intersection between disaster mitigation and sustainable development, particularly in the Indonesian context. With efforts to outline findings related to research trends, map themes, and necessary policy recommendations, this research provides a solid foundation for developing integrated and responsive policy initiatives for disaster mitigation and sustainable development challenges in Indonesia. The findings of this research can provide a more comprehensive and focused view for relevant stakeholders. They can become a basis for further research and policy development to maintain community resilience and advance sustainable development in Indonesia.